PREFACE TO STEM METHODS FOR SCIENCE TEACHERS AT THE DARUL MURSYID ISLAMIC BOARDING SCHOOL: COMMUNITY SERVICE: PENGENALAN METODE STEM BAGI GURU SAINS DI PESANTREN DARUL MURSYID, MEDAN INDONESIA: PENGABDIAN MASYARAKAT - Siregar, Nur Choiro; Nalarsih, Retno Tri (Khidmatuna: Jurnal Pengabdian Masyarakat, 2024)
This preface outlines the community service initiative to enhance Science, Technology, Engineering, and Mathematics (STEM) teaching methodologies for Darul Mursyid Islamic Boarding School science teachers. The initiative's primary objective is to empower educators with advanced STEM strategies, fostering a more engaging and effective learning environment for students. The program aims to balance cultural context with scientific inquiry and critical thinking by integrating traditional educational values with modern STEM practices. Key components include hands-on experiential learning and collaborative professional development through workshops and training sessions. Anticipated outcomes include improved teacher confidence and competence, higher student engagement and achievement in science, and increased interest in STEM careers. The initiative's success will be measured through qualitative feedback and quantitative assessments of student performance. This project underscores the commitment to educational excellence and innovation, setting a benchmark for integrating STEM education within an Islamic educational framework and contributing to broader societal advancement.